Near- and subbarrier elastic and quasielastic scattering of the weakly bound Li6 projectile on Sm144 - Monteiro, D. S. (2009)
High-precision data of backward-angle elastic and quasielastic scattering for the weakly bound Li6 projectile on Sm144 target at deep-sub-barrier, near-, and above-barrier energies were measured. From the deep-sub-barrier data, the surface diffuseness of the nuclear interacting potential was studied. Barrier distributions were extracted from the first derivatives of the elastic and quasielastic excitation functions. It is shown that sequential breakup through the first resonant state of the Li6 is an important channel to be included in coupled-channels calculations, even at deep-sub-barrier energies.